Desenvolvimento de procedimentos em fluxo para a determinação de Captopril, Dipirona e Paracetamol envolvendo multicomutação e inibição da quimiluminêscencia - Oliveira, Geiser Gabriel de (2008)
In the present work, analytical procedures were developed using the multicomutação concept and inhibition of the chemilumenescence for the pharmaceuticals determination, such as, captopril, dipirona and paracetamol. For the control of the analysis module and acquisitions of data a microcomputer was used Pentiun 233 MHz equipped with an electronic interface (PCL - 711S), through programs in language Lab - View 7.0. The detection module consists of a cell of flow of polyethylene (in spiral) of 100 cm, a silicon fotodiodo (OSD-50E) and an electronic device (I model FAC 500), for the conditioning and amplification of the signs chemiluminescents. The analytical procedure was used for captopril determination in pharmaceutical formulations, the system bases on the inhibition of the sign chemiluminescence, between the luminol and the hypochlorite of sodium, when inserting the drug in the system. The analytical curve obtained was linear from 7,5 x 10-6 to 1,0 x 10-4 mol L-1 and detection limit was 9,0 x 10-7 mol L-1 with an analytical frequency of 180 h-1. The same system was used for dipirona determination, that system bases on the oxidation of the dipirona for the hexacianoferrate (III) of potassium, that is the catalyst of the reaction among the luminol-H2O2 happening like this the decrease of the sign quimiluminescente. The analytical curve presented a lineal strip of 1,0 x 10-4 to 9,0 x 10-4 mol L-1 with limit of detection of 9,0 x 10-5 mol L-1 obtaining an analytical frequency of 215 h-1. The studied analytical procedure, for the paracetamol determination in pharmaceutical formulations bases on the consumption of the reagent in excess of hypochlorite of sodium for the drugs, happening from that way to the decrease of the magnitude of the analytical sign. After the optimization of the system it was obtained a lineal strip of answer of 5,0 x 10-6 to 9,0 x 10 -5 mol L-1 with a limit of detection of 2,35 x 10-6 mol L-1 and a frequency of sampling of 180 determinations per hour. In the procedures quimiluminescentes involving multicommutation system stands out the bass consumption of reagents as well as a good analytical frequency.